2008
DOI: 10.1002/er.1378
|View full text |Cite
|
Sign up to set email alerts
|

Ground water level influence on thermal response test in Adana, Turkey

Abstract: SUMMARYFor optimum design of borehole thermal energy storage (BTES) and ground sources heat pump (GSHP) applications, determination of underground thermal properties is required. The design and economic feasibility (number and depth of boreholes) of these systems need thermal conductivity of geological structure, l ðW m À1 K À1 Þ; and thermal resistance of ground heat exchanger, R ðK W À1 mÞ: Thermal properties measured in laboratory experiments do not coincide with data of in situ conditions. Therefore, in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The testing units come in various sizes, ranging from that of a suitcase to a trailer. More detailed descriptions of TRT units can be found in the study by Austin III (1998) and Gehlin and Spitler (2002), and several recent examples of TRT experiments and analysis have been reported (Roth et al 2004; Sanner et al 2005, 2007; Katzenbach et al 2007; Lim et al 2007; Bozdağ et al 2008; Esen and Inalli 2009; Sharqawy et al 2009b). Additional studies reported alternative methods for in situ measurement of the subsurface thermal conductivity, such as the estimation of properties with temperature profiling (Rohner et al 2005), tests performed with heating cables (Heidinger et al 2004; Raymond et al 2010), TRTs that included temperature measurements along the borehole (Fujii et al 2009) and the simulation of a TRT carried out while drilling (Gustafsson 2006).…”
Section: Field Test Methodologymentioning
confidence: 99%
“…The testing units come in various sizes, ranging from that of a suitcase to a trailer. More detailed descriptions of TRT units can be found in the study by Austin III (1998) and Gehlin and Spitler (2002), and several recent examples of TRT experiments and analysis have been reported (Roth et al 2004; Sanner et al 2005, 2007; Katzenbach et al 2007; Lim et al 2007; Bozdağ et al 2008; Esen and Inalli 2009; Sharqawy et al 2009b). Additional studies reported alternative methods for in situ measurement of the subsurface thermal conductivity, such as the estimation of properties with temperature profiling (Rohner et al 2005), tests performed with heating cables (Heidinger et al 2004; Raymond et al 2010), TRTs that included temperature measurements along the borehole (Fujii et al 2009) and the simulation of a TRT carried out while drilling (Gustafsson 2006).…”
Section: Field Test Methodologymentioning
confidence: 99%
“…Groundwater flow can influence heat transfer and an effective thermal conductivity varying, for example, up to 16 % has been found for TRTs carried out under different groundwater flow conditions (Bozdağ et al 2008). TRT with downhole temperature measurements analyzed with infinite line or cylindrical source equations can reveal zones of higher equivalent thermal conductivity that can be associated with groundwater flow if corresponding to facture zones (Fujii et al 2009).…”
Section: Trt Influenced By Groundwater Flowmentioning
confidence: 99%
“…Although numerical tools are available to optimize the operation of a GCHP system under the influence of groundwater flow [5,6], an estimate of the specific groundwater flux affecting a GHE field can be difficult to define accurately. Alternatively, different authors have performed thermal response tests (TRTs) on a single GHE subject to groundwater flow to evaluate the equivalent subsurface thermal conductivity impacted by advection [7,8]. Practitioners commonly using such a heat conduction approach to simulate the long-term operating temperature of GHEs, based on an equivalent subsurface thermal conductivity assumption, have tried to cope with systems influenced by groundwater flow.…”
Section: Introductionmentioning
confidence: 99%